Differences in subcortico-cortical interactions identified from connectome and microcircuit models in autism - Bo-yong Park; Seok-Jun Hong; Sofie L. Valk; Casey Paquola; Oualid Benkarim; Richard A. I. Bethlehem; Adriana Di Martino; Michael P. Milham; Alessandro Gozzi; B. T. Thomas Yeo; Jonathan Smallwood; Boris C. Bernhardt (Nature Communications, 2021)
Autism is increasingly recognized to impact multiple scales of neural organization. Here, the authors show alterations in individuals with autism relative to typically developing controls, with findings particularly pointing to atypically organized subcortical-cortical networks.